CMV Disease of Upper GI Tract in Immunocompetent Host: Two Case Reports and Brief Review of Literature - Mahajan, Nikhil; Sharma, Aproo; Nasa, Mukesh; Lipi, Lipika; Sharma, Rini; Arora, Navleen; Singh, Balwinder (Journal of Digestive Endoscopy, 2020)
Gastrointestinal cytomegalovirus (GI-CMV) infection is well-reported in immunocompromised individuals and those on chemotherapy or other immunosuppressive medications. Rarely, CMV infection of gastrointestinal tract (GIT) occurs in immunocompetent individuals. Colon is the most common site of GI involvement with CMV. However, in immunocompetent individuals, upper GIT involvement is more common. Clinical spectrum of GI-CMV disease is variable and depends on the location and severity of the disease. Prompt diagnosis and treatment aids in reducing morbidity and mortality related to CMV involvement in GI tract. We present two interesting cases of CMV-induced GI ulcers in immunocompetent individuals with brief review of diagnostic and treatment challenges associated with CMV disease in immunocompetent individuals.
Keywords: cytomegalovirus (CMV); esophageal ulcer; gastric ulcer; immunocompetent; upper gastrointestinal tract